2018
DOI: 10.1186/s12875-018-0786-6
|View full text |Cite
|
Sign up to set email alerts
|

Canadian family physician job satisfaction - is it changing in an evolving practice environment? An analysis of the 2013 National Physician Survey database

Abstract: BackgroundTo explore the determinants of job satisfaction and work-life balance satisfaction of family physicians in Canada.MethodsThis is a secondary analysis of the Canadian 2013 National Physician’s Survey using descriptive statistics and binomial logistic regression. An estimated 34,753 family physicians practicing in Canada at the time of survey administration in 2013 were eligible for the survey. The main outcome measures were respondent satisfaction with professional life and satisfaction with work-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…The cross-sectional nature of this study requires future confirmation to better establish causality and to test strategies to reduce physician burnout and job dissatisfaction. Second, in alignment with the response rates of other national physician surveys (17.0%–23.2%),23 49 50 the response rate in this study was only 17.3%. However, non-response bias is less of a concern in surveys of physicians than it is in general population surveys, perhaps because physicians as a group are more homogeneous than are the general public in terms of demographics, knowledge and attitudinal characteristics 51 52.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The cross-sectional nature of this study requires future confirmation to better establish causality and to test strategies to reduce physician burnout and job dissatisfaction. Second, in alignment with the response rates of other national physician surveys (17.0%–23.2%),23 49 50 the response rate in this study was only 17.3%. However, non-response bias is less of a concern in surveys of physicians than it is in general population surveys, perhaps because physicians as a group are more homogeneous than are the general public in terms of demographics, knowledge and attitudinal characteristics 51 52.…”
Section: Discussionsupporting
confidence: 74%
“…Another factor contributing to the stability of the estimates may be the effectiveness of the non-response adjustment weightings for the sample of physician respondents 53. We constructed probability weights to adjust for potential bias 23 50 53…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, increased satisfaction with work has been reported from doctors in the Netherlands from 2000 to 200948 and from six graduation cohorts from 1996 to 2012 in the UK 49. High levels of job satisfaction were documented from emergency medicine residents in the USA,50 family physicians in Canada,51 primary care physicians in Germany52 and doctors in Australia 53…”
Section: Discussionmentioning
confidence: 99%
“…An American study on physicians found that dissatisfaction with the EHR was associated with intent to reduce clinical work hours and to leave the current practice [ 26 ]. A Canadian study on family physicians’ job satisfaction found that the use of an EHR was negatively associated with both processional and work–life balance satisfaction [ 27 ], and an American study found that an increase in satisfaction on EHR use increased also job satisfaction among family physicians [ 28 ]. An American study found electronic medical record requirements as one of the six main themes emerging amongst qualitative interviews of 26 family physicians about job satisfaction and burnout [ 29 ].…”
Section: Introductionmentioning
confidence: 99%